Diversity of Deep-Sea Scale-Worms (Annelida, Polynoidae) in the Clarion-Clipperton Fracture Zone - Bonifácio, Paulo; Neal, Lenka; Menot, Lénaïck (Frontiers in Marine Science, 2021)
The polymetallic nodules lying on the seafloor of the Clarion-Clipperton Fracture Zone (CCFZ) represent over 30 billion metric tons of manganese. A single mining operation has potential to directly impact approximately 200 km2 of the seabed per year. Yet, the biodiversity and functioning of the bentho-demersal ecosystem in the CCFZ remain poorly understood. Recent studies indicate a high species diversity in a food-poor environment, although the area remains poorly sampled. Undersampling is aggravated by a combination of low densities of fauna and high habitat heterogeneity at multiple spatial scales. This study examines the Polynoidae, a diverse family of mobile polychaetes. Sampling with an epibenthic sledge and a remotely operated vehicle was performed during the cruise SO239 within the eastern CCFZ. Five areas under the influence of a sea surface productivity gradient were visited. Specimens were identified using morphology and DNA: (i) to provide a more comprehensive account of polynoid diversity within the CCFZ, (ii) to infer factors potentially driving alpha and beta diversity, and (iii) to test the hypothesis that epibenthic polychaetes have low species turnover and large species range. Patterns of species turnover across the eastern CCFZ were correlated with organic carbon fluxes to the seafloor but there was also a differentiation in the composition of assemblages north and south of the Clarion fracture. In contrast to the previous studies, patterns of alpha taxonomic and phylogenetic diversity both suggest that polynoid assemblages are the most diverse at Area of Particular Environmental Interest no. 3, the most oligotrophic study site, located north of the Clarion fracture. Without ruling out the possibility of sampling bias, the main hypothesis explaining such high diversity is the diversification of polynoid subfamily Macellicephalinae, in response to oligotrophy. We propose that macellicephalins evolved under extremely low food supply conditions through adoption of a semi-pelagic mode of life, which enabled them to colonise new niches at the benthic boundary layer and foster their radiation at great depths.